PENGARUH PROMOSI MEDIA SOSIAL, ELECTRONIC WORD OF MOUTH DAN BRAND PREFERENCE TERHADAP KEPUTUSAN PEMBELIAN KOPI MANG ENCAK - Fera Kartika; Tri Lestira Putri Warganegara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of social media and digital technology has encouraged businesses to utilize online-based marketing strategies to influence consumer purchasing decisions. This study aims to analyze the influence of social media promotion, Electronic Word of Mouth (E-WOM), and Brand Preference on purchasing decisions at Kopi Mang Encak in West Lampung. This study used a quantitative approach with a causal associative research method. Data were obtained by distributing questionnaires to 98 respondents, who are consumers of Kopi Mang Encak, using an accidental sampling technique. Data analysis methods used included validity testing, reliability testing, normality testing, multiple linear regression analysis, t-tests, and F-tests. The results showed that partially, social media promotion, Electronic Word Of Mouth, and Brand Preference had a positive and significant effect on purchasing decisions for Kopi Mang Encak. Simultaneously, these three independent variables also had a significant effect on purchasing decisions.